1999
DOI: 10.1128/mcb.19.3.2069
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Chaperone Activity of Heat Shock Protein 70 and Thermotolerance

Abstract: Heat shock protein 70 (Hsp70) is thought to play a critical role in the thermotolerance of mammalian cells, presumably due to its chaperone activity. We examined the chaperone activity and cellular heat resistance of a clonal cell line in which overexpression of Hsp70 was transiently induced by means of the tetracyclineregulated gene expression system. This single-cell-line approach circumvents problems associated with clonal variation and indirect effects resulting from constitutive overexpression of Hsp70. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
142
0
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(150 citation statements)
references
References 43 publications
3
142
0
5
Order By: Relevance
“…4b) and due to the expression of co-chaperones. However, Nollen et al (1999) reported that thermotolerant cells were more resistant to heat than cells expressing identical levels of Hsp72.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4b) and due to the expression of co-chaperones. However, Nollen et al (1999) reported that thermotolerant cells were more resistant to heat than cells expressing identical levels of Hsp72.…”
Section: Resultsmentioning
confidence: 99%
“…Thermotolerant L929 cells that express endogenous Hsp72, showed significant protection against luciferase denaturation. The increased protection of luciferase activity in thermotolerant cells compared to cells expressing transgenic Hsp72 has already been noted (Nollen et al 1999) and is probably related to the presence of additional chaperone and co-chaperone proteins in thermotolerant cells (Craig 1985).…”
Section: Discussionmentioning
confidence: 99%
“…High temperature or heat stress has been found to induce an increase in HSP protein production in certain tissues [22]. HSP 70 stimulates proliferation of some types of tumor cells [6], and it has been found to be an anti-apoptotic protein that inhibits cell death by apoptosis in human and canine mammary gland tumor cells [18] and human prostatic adenocarcinama cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…A high ROS concentration in the cryptorchid testis is an important risk factor for the occurrence and development of testicular tumors [29]. Heat shock protein (HSP) 70 is the main protein produced abundantly in some tissues exposed to heat stress [22], and it induces the development of certain tumors [6,18,20]. Inhibin (INH) in male animals is a glycoprotein produced by Sertoli cells [23,24,28] and is composed of two subunits, an α-unit and a β-unit [8,23].…”
mentioning
confidence: 99%
“…15 and 21 for review). In fact, aggregation of nuclear proteins as well as a reporter enzyme (firefly luciferase) after heat shock was reduced in thermotolerant cells expressing HSPs, and these cells demonstrated faster solubilization of aggregated proteins during the recovery period (2,26,42,53). Furthermore, expression of HSP72 (the major inducible member of the HSP70 family) alone was sufficient to reduce nuclear protein aggregation and accelerate refolding of luciferase after heat shock (42, 54).…”
mentioning
confidence: 99%